Do we know what content students learn in Phisical Education? - S. Del Valle; L.M. Ruíz; R. De la Vega; R. Velázquez; P. Díaz (Asociación Española de Ciencias del Deporte, 2010)
The main objective of this study was analyze the impact of different interventions programs in the declarative and procedimiental knowledge of student at the Secondary Education measured with a CONTEF questionnaire. Students were divided into two groups, one of them called "experimental" (without any experience in practicing with a reflective methodology) and the other one called "control" (with 3 years of experience in the use of a cooperative methodology). This study was carry out during the school year 2002-2003 and results showed that the "experimental" group obtained better results in the learning of conceptual and procedimiental contents in relation to the "control" group, mainly for the affective and social aspects of these learning. PALABRAS CLAVE: Significant learning, reflective methodology, awareness, knowledge, physical education.